Using Positive and Negative Peace Theory To Analyse the American “Culture Wars” During the Trump Era - Nadeau, Josh (Université d'Ottawa | University of Ottawa, 2023)
This thesis proposes that Johan Galtung’s theory of positive and negative peace will gain relevance and applicability in contexts of non-armed societal conflicts like the Trump-era culture wars when the theory is adapted to take into account not only dynamics such as violence, but also felt threat. In this project, I reviewed the academic literature on culture war and sociopolitical polarization in the United States, as well as the literature on Galtung’s theory. I then adapted positive and negative peace theory to take into account conflict dynamics rising from felt threat, which I argue makes Galtung’s theory more applicable to conflicts where violence is invisible, contested or difficult to ascertain. I tested this version of Galtung’s theory through 20 exploratory, qualitative interviews with American liberal and conservative partisans. These interviews resulted in a typology of various a) visions of positive and negative peace in the Trump-era culture wars, b) strategies partisans use to achieve them and c) preferences for specific types of peace. These results are discussed regarding their relevance to the field and their contribution to the academic literature.
Keywords: positive and negative peace; culture war; sociopolitical polarization; Donald Trump; peacebuilding